2.5D quartz fabric reinforced nanoporous phenolic composites with weakened heat transfer and optimized mechanical properties. (10th November 2022) - Niu, Bo; Shen, Haochen; Li, Tong; Zhang, Hongyu; Qian, Zhen; Cao, Yu; Zhang, Yayun; Long, Donghui
Abstract: Phenolic-based composites are the most promising ablative thermal protection materials for space applications, but optimizing their thermal insulation performance while maintaining high strength remains extremely challenging. Herein, phenolic-based composites with co-optimized thermal insulation and mechanical properties are prepared via 2.5D quartz fabric reinforcing nanoporous phenolic. The pore size of phenolic matrix is efficiently refined to ∼35 nm by adjusting resin concentration, enabling composites to exhibit high density but low thermal conductivity by enhancing Knudsen diffusion. Finite element analysis shows that low braiding angle of 2.5D fabric can further weakening heat transfer of composites due to anisotropic thermal conductivity of fiber yarns. In-situ X-ray micro-CT results indicate that 2.5D fabrics can reinforce composites through interwoven yarns, and straighter weft yarns result in higher strength along weft direction than that along warp direction. Compared with dense quartz/phenolic composite, the resulting composites exhibit 16.5% lower density (1.32 g/cm 3 ), 58.8% lower thermal conductivity (0.21 W/(m·K), ≥372.7% higher tensile strength (≥182.0 ± 9.6 MPa) and comparable ablation resistance. The present results will further advance the application of phenolic-based composites in more extreme re-entry environments. Graphical abstract: Image 1